Imagine There's No President: The Rhetorical Secret and the Exposure of Valerie Plame - Hallsby, Atilla (The Quarterly journal of speech, 2015)
Covering a wide range of public discourse from 2003 to 2010 about CIA agent Valerie Plame, this essay contributes a novel rhetorical theory of secrets. By contrast to other critiques of the Bush-era secrecy that focus on policies the administration kept concealed from the public, I suggest that rhetoric is the means by which subjects figure the secret, to be understood as knowledge in the fact that the subject cannot know. To make this argument, I draw on the theoretical tools of psychoanalysis and the rhetorical tropes of repetition, caesura, and synecdoche.